Motivational approaches in construction industries : a literature review / Asniza Hamimi Abdul Tharim, Farah Wahida Hashim and Asmalia Che Ahmad - Abdul Tharim, Asniza Hamimi; Hashim, Farah Wahida; Che Ahmad, Asmalia (2012)
Motivation is a natural urge maker that makes us feel ease and sincere in doing our work. Workers with low motivation will be stress and doing their work just to get their pay. They will not enjoy the moment they spent in the office and the stress will be brought back to home. As result, they are not only failed to be a good worker but completely ruining their live. It will affect their quality time at home and slowly risking their health. Every employee owns high responsibility to their employer especially for the construction industry‟s employees‟ as their performance indicates the quality of the building built. The purpose of this research is to identify the motivational approaches that can be use to enhance the productivity of employees in contractors organizations besides of producing a high quality building. The objective of this paper is to identify types of motivational approaches in construction industries focusing out contractors‟ companies.